Device Architecture Engineering: Progress toward Next Generation Perovskite Solar Cells. (23rd June 2021) - Webb, Thomas; Sweeney, Stephen J.; Zhang, Wei
Abstract: Over the past decade, perovskite solar cells (PSCs) have quickly established themselves as a promising technology boasting both high efficiency and low processing costs. The rapid development and success of PSCs is a product of substantial research effort addressing compositional engineering, thin film fabrication, surface passivation, and interfacial treatments. Recently, engineering of device architecture has entered a renaissance with the emergence of several new bulk and graded heterojunction structures. These structures promote a lateral approach to the development of single‐junction PSCs affording new opportunities in light management, defect passivation, carrier extraction, and long‐term stability. Following a short overview of the historic evolution of PSC architectures, a detailed discussion of the promising progress of the recently reported perovskite bulk heterojunction and graded heterojunction approaches are offered. To enable better understanding of these novel architectures, a range of approaches to characterizing the architectures are presented. Finally, an outlook and perspective are provided offering insights into the future development of PSC architecture engineering. Abstract : Four emerging perovskite structures that have origins in pre‐existing technologies such as silicon and chalcogenide‐based photovoltaic cells are reviewed. The implementation of the new architectures holds great promise in reducing transport losses, light management, and stability. To guide further research into these areas key design criteria are identified and key characterization methods discussed.